Concepts of Space, Refiguration of Spaces, and Comparative Research: Perspectives from Economic Geography and Regional Economics - Lech Suwala (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2021)
Following the concept of refiguration of spaces proposed by KNOBLAUCH and LÖW (2017), in this article I emphasize interfaces for theory building, methods, and comparative research from an economic geography and regional economics perspective. Since the refiguration of spaces offers an abstract frame capable of grasping spatial relations of any order and across various scales, I will discuss the utilization of concepts of space in both subdisciplines by employing a textbook analysis. Moreover, I will include two examples of current economic phenomena where refiguration takes place. Namely, I will analyze the internationalization of companies and world trade interdependencies according to concepts of space, their implication on methods, and comparative research. In my findings, I show that the abstract frame of refiguration of spaces unlocks great potential if applied consistently. Economic geography has a great deal to offer for the micro-foundation in the refiguration of spaces, working with qualitative methods and forward thinking concepts of space (e.g., relational or topical points of view for comparison). Regional economics allows for progress concerning the macro-foundation in the refiguration of spaces through the increased availability of regional or big data and advanced quantitative methods (e.g., manifold indexes capturing refiguration).
Keywords: R10; R11; R58; P25; P48; B00; F13; F23; B59; A12; D21; B41; A20; R13; F60; 330; refiguration of spaces; concepts of space; economic geography; regional economics; comparative research; spatial analysis; internationalization of companies; world trade interdependencies